1997
DOI: 10.1136/gut.41.3.330
|View full text |Cite
|
Sign up to set email alerts
|

Rectal cell proliferation and colon cancer risk in patients with hypergastrinaemia

Abstract: Background-The influence of gastrin on the colonic mucosa is still uncertain. Some authors have suggested a stimulating eVect on the growth of normal and malignant colonic epithelium, while others have shown no association between gastrin and neoplastic development. Aims-To evaluate the eVect of gastrin on colorectal cell proliferation, patients with chronic endogenous hypergastrinaemia underwent proctoscopy. Biopsy specimens were taken in order to study rectal cell kinetics. Patients and controls-Ten patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 23 publications
0
43
1
1
Order By: Relevance
“…54 In certain disease states, such as Zollinger-Ellison syndrome, elevated plasma levels of nonamidated gastrins have been measured 30,31,55 ; these elevated levels may result in a predisposition toward colonic malignancy in a subpopulation of patients who also are positive for other associated risk factors. Hypergastrinemia reportedly is associated with mitogenic effects on colorectal mucosae 56,57 and with an increased risk of colonic malignancy 57,58 in a subpopulation of patients. Thus, there is good reason to believe that in patients with hypergastrinemia, circulating PG may play an important role in the initial stages of colon carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…54 In certain disease states, such as Zollinger-Ellison syndrome, elevated plasma levels of nonamidated gastrins have been measured 30,31,55 ; these elevated levels may result in a predisposition toward colonic malignancy in a subpopulation of patients who also are positive for other associated risk factors. Hypergastrinemia reportedly is associated with mitogenic effects on colorectal mucosae 56,57 and with an increased risk of colonic malignancy 57,58 in a subpopulation of patients. Thus, there is good reason to believe that in patients with hypergastrinemia, circulating PG may play an important role in the initial stages of colon carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of patients with classical causes of hypergastrinemia such as Zollinger-Ellison syndrome or pernicious anemia have suggested that, although colonic mucosal proliferative rates are increased, tumors do not occur more commonly. [37][38][39][40] The possibility should also be considered that immature gastrins rather than gastrin amide may be responsible for the hyperproliferative colonic mucosa in such hypergastrinemic states. 41,42 Although the available data is limited, serum concentrations of progastrin and glycine-extended intermediates are elevated in patients with Zollinger-Ellison syndrome, in greater proportion than gastrin amide.…”
Section: Discussionmentioning
confidence: 99%
“…The nonspecific gastrin inhibitors proglumide and benzotript, which appear to bind the 78-kDa potential receptor for the incompletely processed forms of gastrin (24), can inhibit the growth of colon cancer cell lines (25) as well as transplanted colon carcinomas (26). Patients with Zollinger-Ellison syndrome, which results in elevated levels of circulating amidated gastrin, G-Gly, and progastrin, also have increased colonic proliferation rates and a shift in the proliferative zone into the upper third of the crypt (27,28). Increased colonic proliferation and the expansion of the proliferative zone into the upper third of the crypt have been associated with an increased risk of developing colon cancer in humans (29,30).…”
Section: Introductionmentioning
confidence: 99%